Clinical outcomes in COVID-19 patients with in-hospital cardiac arrest – an insight from multi-centre data. (14th October 2021) - Mughal, M; Kaur, I; Waxman, S; Gandhi, H; Kakadia, M; Khakwani, Z; Okoh, A; Shah, K; Obaid, A; Sirpal, V; Azad, S; Jaffery, A; et al.
Abstract: Background: In general, rates of in-hospital cardiac arrest are reportedly 9 to 10 arrests per 1000 admissions, with survival rates of approximately 20–25%. Data regarding clinical characteristics and outcomes in patients with COVID-19 who received in-hospital CPR (cardiopulmonary resuscitation) are limited. This information can help guide end-of-life care conversations between families and health care workers based on real-world experience. Purpose: To observe the outcomes (survival to discharged alive from the hospital) in critically sick COVID-19 patients who experienced in-hospital cardiac arrest. Methods: This is a multi-centre institutional review board (IRB) approved retrospective study. The RT-PCR confirmed adult COVID-19 patients consecutively admitted from March 1st to April 30, 2020, were included. Data were extracted manually using the hospital's electronic medical record. The final date of follow-up to monitor clinical outcomes was January 2021. Results: A total of 721 patients were admitted to the hospital. Of these, only 64 (8.87%) patients had "no CPR" orders.Cardiac arrest occurred in 141 (19.5%) patients. The mean duration of beginning of resuscitation was less than a minute and the mean duration of CPR was 19 minutes. The median age was 65 years; 62.4% were male. The most common co-morbidities were hypertension (66%) and diabetes mellitus (56%). The initial rhythm was non-shockable in 93.7% of patients [asystole in 48.4% and Pulseless Electrical Activity (PEA) in 45.3% of patients]. Only six (4.2%) patients had pulseless ventricular tachycardia and three (2.1%) patients had ventricular fibrillation. A total of eight patients (5.6%) survived and were discharged from the hospital; six (4.25%) had non-shockable and two (0.82%) had shockable initial rhythms. The median age of those who survived was 60 years (Figure 1). Conclusions: Our study showed that critically sick patients with COVID-19 have a high rate of cardiac arrest and poor outcomes in those who received CPR. A non-shockable initial rhythm indicates that non-cardiac reasons might be playing a major role. These include acute respiratory insufficiency, severe sepsis, or multiorgan failure. These data should inform end-of-life care discussions between providers and patients' families. FUNDunding Acknowledgement: Type of funding sources: None.